PERTANGGUNG JAWABAN NOTARIS DALAM HAL TERJADINYA PENGGELAPAN DOKUMEN OLEH PEGAWAI KANTOR NOTARIS - ALIFFIADARA MELYZA AYUWI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Dr. mahmud Mulyadi, SH, MHumA notary needs employess in carrying out his professional duties to organize office administration. The employees ideally are expected to have criteria such as being responsible, conscientious, honest, having knowledge of notarial affairs and being able to keep the confidentiality of the content of the deeds. However, in reality, the expected criteria do not alwasy fit the notary’s expectation. One of the cases is found in Langsa, in which an employee at a Notary’s office did a criminal act of embezzlement with his authority. The objective of the research is to analyze the criminal act of document embezzlement done by the employee at notary’s office, the injuries endured by the notary, and how the form of notary’s responsibility for the criminal act of embezzlement done by his employee. This research employs normative juridical method with analytical description. It uses secondary data to answer the research problems. The data are collected through library study and interview results. The results of the research present that the criminal act of document embezzlement done by the employee at a noptary’s office lasted for 6 (six) months. There were 77 (seventy seven) ex-administrative documents found in the search. The Notary was materially, immaterially, and financially injured by the embezzlement done by his employee; thus, he was the one taking the responsibility to complete the clients’ deeds and administrative documents It is suggested that the notary organize a selection of employee candidates very carefully to reduce the risks in the administrative flow at his office which is risky; and realize the number of state documents which confidentiality has to be protected. In case something happens to the documents, the notary will be mostly responsible, so that it is necessary to make extra supervision to the employees’ performance for the continuitu and professionalism of the notary’s office.Keywords: Ruling, Criminal Act of Embezzlement, Notary, Notary’s Employee